2019
DOI: 10.15835/buasvmcn-vm:2018.0049
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Growth Traits and Tibiae Health in Sexed Indigenous Turkeys with Different Feather Colours Under Deep Litter and Outdoor Run Houses

Abstract: The study consisted of 400 sexed turkeys, grouped on the basis of 2 distinct feather colours (white and black) into deep litter and outdoor, respectively. Day-old poults were brooded for 4 weeks and acclimatized in both houses for 2 weeks before the commencement of the study that lasted for 10 weeks. At the end of the trial, 2 birds per replicate were sacrificed and left tibiae were removed for morphometric and mineral analyses. Data were arranged in a 2 × 2 × 2 factorial layout and subjected to Analysis of Va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 26 publications
3
0
0
Order By: Relevance
“…Lower values of RI represent more robust bones. Similar to the current findings, a recent study described significantly different RIs between male and female turkeys (Safiyu et al, 2019). Safiyu et al (2019) showed similar results for production systems in which deep litter and free-range systems did not change the RI of turkeys.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Lower values of RI represent more robust bones. Similar to the current findings, a recent study described significantly different RIs between male and female turkeys (Safiyu et al, 2019). Safiyu et al (2019) showed similar results for production systems in which deep litter and free-range systems did not change the RI of turkeys.…”
Section: Resultssupporting
confidence: 91%
“…Similar to the current findings, a recent study described significantly different RIs between male and female turkeys (Safiyu et al, 2019). Safiyu et al (2019) showed similar results for production systems in which deep litter and free-range systems did not change the RI of turkeys. According to the literature, heavier birds have abnormally developed bones with high porosity and much lower density, which make them less robust than lightweight birds (Bennett, 2008).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation